Factors that influence consumer ethics in purchasing process of pirated VCDs and CDs / Nurul Liyana Sapee - Sapee, Nurul Liyana (2011)
This study explores the factors influencing consumer ethical in purchasing process of pirated vcds or cds. 50 questionnaires were distributed among potential respondents for this study, of which all were returned. After completing the screening process, all the responses were considered complete and valid to undergo data analysis. The results of this study showed that there is a significant relationship between consumer moral judgments, social influence, and price or value consciousness towards the consumer ethical decision making when purchasing pirated vcds or cds. The outcome of this research showed a comprehensively integrated framework allowing policy makers and responsible parties to explore dimensions like moral judgment, social influence and price or value consciousness and their effect on the consumer’s decision making in purchasing pirated vcds or cds. However, further research is needed to examine these factors in Malaysia with additional samples before generalizations can be accurately made